Evaluation of IFNAR2 and TYK2 transcripts’ prognostic role in COVID-19 patients: a retrospective study - Razavi, Alireza; Raei, Maedeh; Hatami, Yasin; Chokami, Ghazal Saghi; Goudarzi, Yasaman; Ghasemian, Roya; Alizadeh-Navaei, Reza; Yarmohammadi, Hossein; Soltanipur, Masood; Tabarestani, Mohammad; Valadan, Reza; Meshkinfam Haghighi, Faranak; et al. (Frontiers in Cellular and Infection Microbiology, 2024)
Background and objectives This study aimed to investigate the possible prognostic significance of interferon alpha–beta receptor subunit 2 (IFNAR2) and tyrosine kinase 2 (TYK2) expressions. Methods We conducted a retrospective study including COVID-19 adult patients. All blood samples were collected before any interventions. The expressions of IFNAR2 and TYK2 were assessed using real-time PCR in venous blood samples of 54 cases and 56 controls. The transcript quantities of IFNAR2 and TYK2 genes were assessed using a Delta-Ct method. Results Our findings show no significant differences in gene expression levels for IFNAR2 and TYK2 between patients who required oxygen (O2) therapy and those who did not (p-value = 0.732 and p-value = 0.629, respectively). Likewise, there were no significant differences in IFNAR2 and TYK2 expressions between patients hospitalized for less than 7 days and those hospitalized for 7 days or more (p-value = 0.455 and p-value = 0.626, respectively). We also observed a weak correlation between IFNAR2 expression and CRP (p-value = 0.045, r = 0.192). There was a negative correlation between the expression levels of IFNAR2 and TYK2 transcripts in COVID-19 patients (p-value = 0.044; partial correlation coefficient = -0.283). Additionally, IFNAR2 and TYK2 were significantly downregulated in the COVID-19 group compared to healthy subjects (p-value = 0.002 and p-value = 0.028, respectively). However, neither IFNAR2 nor TYK2 expression was significantly different between the case subgroups based on COVID-19 severity. The IFNAR2 ΔΔCt (B = -0.184, 95% CI: -0.524–0.157, p-value = 0.275) and the TYK2 ΔΔCt (B = 0.114, 95% CI: -0.268–0.496, p-value = 0.543) were not found to be significant predictors of hospitalization duration. The area under the curve (AUC) for IFNAR2 expression is 0.655 (p-value = 0.005, 95% CI: 0.554–0.757), suggesting its poor discriminative value. Conclusion We were unable to comment definitively on the prognostic power of IFNAR2 and TYK2 expressions in COVID-19 patients, and larger-scale studies are needed. The principal limitations of this study included the lack of longitudinal analysis and limited sample size.